Urge intolerance predicts tic severity and impairment among adults with Tourette syndrome and chronic tic disorders - Ramsey, Kesley A.; De Nadai, Alessandro S.; Espil, Flint M.; Ricketts, Emily; Stiede, Jordan T.; Schild, Jennifer; Specht, Matthew W.; Woods, Douglas W.; Bennet, Shannon; Walkup, John T.; Chang, Susanna; Piacentini, John; et al. (Frontiers in Psychiatry, 2022)
Background: Individuals with Tourette Syndrome and Persistent Tic Disorders (collectively TS) often experience premonitory urges—aversive physical sensations that precede tics and are temporarily relieved by tic expression. The relationship between tics and premonitory urges plays a key role in the neurobehavioral treatment model of TS, which underlies first-line treatments such as the Comprehensive Behavioral Intervention for Tics (CBIT). Despite the efficacy of CBIT and related behavioral therapies, less than 40% of adults with TS respond to these treatments. Further examination of the relationship between premonitory urges, tic severity, and tic impairment can provide new insights into therapeutic targets to optimize behavioral treatment outcomes. This study examined whether urge intolerance—difficulty tolerating premonitory urges—predicted tic severity and tic-related impairment among adults with TS. Methods: Participants were 80 adults with TS. Assessments characterized premonitory urge, distress tolerance, tic severity, and tic impairment. We used structural equation modeling (SEM) to examine the construct of urge intolerance—comprised of premonitory urge ratings and distress tolerance ratings. We first evaluated a measurement model of urge intolerance through bifactor modeling, including tests of the incremental value of subfactors that reflect premonitory urge severity and distress tolerance within the model. We then evaluated a structural model where we predicted clinician-rated tic severity and tic impairment by the latent variable of urge intolerance established in our measurement model. Results: Analyses supported a bifactor measurement model of urge intolerance among adults with TS. Consistent with theoretical models, higher levels of urge intolerance predicted greater levels of clinician-rated tic severity and tic impairment. Conclusion: This investigation supports the construct of urge intolerance among adults with TS and distinguishes it from subcomponents of urge severity and distress tolerance. Given its predictive relationship with tic severity and tic impairment, urge intolerance represents a promising treatment target to improve therapeutic outcomes in adults with TS.